The Risk of Atherosclerotic Cardiovascular Disease among Hyperlipidaemia Patients and Appropriateness of Statin Therapy - Iskandar, Maharani F.; Nurmainah, Nurmainah; Susanti, Ressi (Pharmacology and Clinical Pharmacy Research)
Patients with hyperlipidaemia is at increased risk of developing atherosclerotic cardiovascular disease (ASCVD). The use of appropriate statin therapy is important to obtain optimal health outcomes. However, there was limited information regarding the risk of ASCVD among Indonesian hyperlipidaemia population and the appropriateness of statin therapy given to these patients. This study aimed to assess the ASCVD risks among the patients and evaluate the use of statin therapy at hospitalized hyperlidaemia patients. This cross sectional study used medical records as data source. This study was conducted at one hospital in Pontianak, Indonesia during Januari-June 2017. We included 50 subjects. The 10-year risk of ASCVD was assessed using ASCVD pooled cohort risk assessment equation (PCRAE). The results showed that 66% of the included subjects had a relatively high risk of developing ASCVD. Subjects with high risk of ASCVD received inappropriate statin therapy. High intensity statin should be given to these patients. In conclusion, large proportion of the subjects were at high risk of developing ASCVD. Nevertheless, inappropriate statin therapy were given to these patients. Improvement in medication practice should be done to prevent complication and increase quality of health outcomes.Keywords: ASCVD, dyslipidemia, statin